USP18 lack in microglia causes destructive interferonopathy of the mouse brain. (20th April 2015) - Goldmann, Tobias; Zeller, Nicolas; Raasch, Jenni; Kierdorf, Katrin; Frenzel, Kathrin; Ketscher, Lars; Basters, Anja; Staszewski, Ori; Brendecke, Stefanie M; Spiess, Alena; Tay, Tuan Leng; Kreutz, Clemens; et al.
Abstract Microglia are tissue macrophages of the central nervous system (CNS) that control tissue homeostasis. Microglia dysregulation is thought to be causal for a group of neuropsychiatric, neurodegenerative and neuroinflammatory diseases, called "microgliopathies". However, how the intracellular stimulation machinery in microglia is controlled is poorly understood. Here, we identified the ubiquitin‐specific protease (Usp) 18 in white matter microglia that essentially contributes to microglial quiescence. We further found that microglial Usp18 negatively regulates the activation of Stat1 and concomitant induction of interferon‐induced genes, thereby terminating IFN signaling. The Usp18‐mediated control was independent from its catalytic activity but instead required the interaction with Ifnar2. Additionally, the absence of Ifnar1 restored microglial activation, indicating a tonic IFN signal which needs to be negatively controlled by Usp18 under non‐diseased conditions. These results identify Usp18 as a critical negative regulator of microglia activation and demonstrate a protective role of Usp18 for microglia function by regulating the Ifnar pathway. The findings establish Usp18 as a new molecule preventing destructive microgliopathy.